New Model of Maximal Covering Location Problem with Fuzzy Conditions - Drakulić, Darko; Takači, Aleksandar; Marić, Miroslav (Computing and Informatics, 2016)
The objective of Maximal Covering Location Problem is locating facilities such that they cover the maximal number of locations in a given radius or travel time. MCLP is applied in many different real-world problems with several modifications. In this paper a new model of MCLP with fuzzy conditions is presented. It uses two types of fuzzy numbers for describing two main parameters of MCLP - coverage radius and distances between locations. First, the model is defined, then Particle Swarm Optimization method for solving the problem is described and tested.